Situation Report: Czechoslovakia, 6 July 1966 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Eleventh Plenary Session of the National Assembly Hendrych's Speech at the Party Central Committee School of Politics Novotny Interviewed by Lord Thomson Meeting of the Slovak Party Central Committee Goldmann on the Further Growth of the Czechoslovak Economy News in Brief